Treatment modalities and evaluation models for periodontitis - Tariq, Mohammad; Iqbal, Zeenat; Ali, Javed; Baboota, Sanjula; Talegaonkar, Sushama; Ahmad, Zulfiqar; Sahni, Jasjeet K (International Journal of Pharmaceutical Investigation)
Periodontitis is the most common localized dental inflammatory disease related with several pathological conditions like inflammation of gums (gingivitis), degeneration of periodontal ligament, dental cementum and alveolar bone loss. In this perspective, the various preventive and treatment modalities, including oral hygiene, gingival irrigations, mechanical instrumentation, full mouth disinfection, host modulation and antimicrobial therapy, which are used either as adjunctive treatments or as stand-alone therapies in the non-surgical management of periodontal infections, have been discussed. Intra-pocket, sustained release systems have emerged as a novel paradigm for the future research. In this article, special consideration is given to different locally delivered anti-microbial and anti inflammatory medications which are either commercially available or are currently under consideration for Food and Drug Administration (FDA) approval. The various in vitro dissolution models and microbiological strain investigated to impersonate the infected and inflamed periodontal cavity and to predict the in vivo performance of treatment modalities have also been thrashed out. Animal models that have been employed to explore the pathology at the different stages of periodontitis and to evaluate its treatment modalities are enlightened in this proposed review.
Keywords: Chemotherapeutic agents; intra-pocket devices; mechanical therapies; oral hygiene